Instruction of poetry writing in normal students and students with special needs through readers’ response and cultural studies approach - Saraswati, Ekarini; Budiman, Ajang (Journal of Community Service and Empowerment, 2020)
SMP Muhammadiyah 2 Malang is high school that receives many students with special needs. There are around 30 students with speacial needs distributed in several classes out of a total of 224 students. In this regard, the problem to reveal is about the instruction to write poetry in normal students and students with special needs. The objectives of this community service program are (1) to improve the importance of poetry writing instruction at school for soft character building; (2) to improve teachers’ understanding of individual learning on poetry; (3) to improve students’ ability to write poetry by expanding their horizon through pictures. The method implemented in this program were: (1) training poetry writing using cultural study approach through video; (2) training on poetry writing, and (3) mentoring. All these methods are integral part of the PPMI program. The outcomes of this program are: (1) community service team: a. Video about Malang and journal article 2. School Partner: lesson plan using socio cultural approach b. Poem written by students. The results of this program show that the poems written by students show love for Malang. In addition, the poems written individually and video displaying pictures of Malang from the royal era until now have added students’ insight.